The effectiveness of the Malaysian nationhood course in encouraging patriotism among students in institutions of higher education: a preliminary report - Ku Samsu, Ku Hasnita; Ahmad, Noor Shafiza (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This study was designed to analyze and compare the level of patriotism awareness among students before and after completing the Malaysian Nationhood course. In order to realize this preliminary report, the data which had been collected from a pilot survey will be used to achieve the objectives of this study. There were thirty respondents involved in the pilot survey which was conducted in Universiti Putra Malaysia. The data collection had been conducted in two phases, namely pre-test and post-test and analyzed using descriptive statistical analysis such as means, percentage and frequency. Additionally, inferential statistical analysis that is paired sample t-test, was also used.